Syntheses and Characterization of a Pair of Isomers of Heteroleptic Bis(Bidentate) Ruthenium(II) Complexes with Two Different Monodentate Ligands. Issue 72 (14th November 2019) - Toyama, Mari; Takizawa, Takako; Morita, Itaru; Nagao, Noriharu; Kuramochi, Yusuke; Ishida, Hitoshi
Abstract: Two isomers of heteroleptic bis(bidentate) ruthenium(II) complexes with dimethyl sulfoxide (dmso) and chloride ligands, trans (Cl, Nbpy )‐ and trans (Cl, NHdpa )‐[Ru(bpy)Cl(dmso‐ S )(Hdpa)] + (bpy: 2, 2′‐bipyridine; Hdpa: di‐2‐pyridylamine), are synthesized. This is the first report on the selective synthesis of a pair of isomers of cis ‐[Ru(L)(L′)XY] n + (L≠L′: bidentate ligands; X≠Y: monodentate ligands). The structures of the ruthenium(II) complexes are clarified by means of X‐ray crystallography, and the signals in the 1 H NMR spectra are assigned based on 1 H– 1 H COSY spectra. The colors of the two isomers are clearly different in both the solid state and solution: the trans (Cl, Nbpy ) isomer has a deep red color, whereas the trans (Cl, NHdpa ) isomer is yellow. Although both complexes have intense absorption bands at λ ≈440–450 nm, only the trans (Cl, Nbpy ) isomer has a shoulder band at λ ≈550 nm. DFT calculations indicate that the LUMOs of both isomers are the π* orbitals in the bpy ligand, and that the LUMO level of the trans (Cl, Nbpy ) isomer is lower than that of the trans (Cl, NHdpa ) isomer due to the trans effect of the Cl ligand; thus resulting in the appearance of the shoulder band. The HOMO levels are almost the same in both isomers. The energy levels are experimentally supported by cyclic voltammograms, in which these isomers have different reduction potentials and similar oxidation potentials. Abstract : Color check : A pair of isomers of heteroleptic bis(bidentate) ruthenium(II) complexes with two different monodentate ligands have been synthesized. trans (Cl, Nbpy )‐[Ru(bpy)Cl(dmso‐ S )(Hdpa)] + (bpy: 2, 2′‐bipyridine; Hdpa: di‐2‐pyridylamine) has a deep red color, whereas the trans (Cl, NHdpa ) isomer is yellow. These results are discussed with respect to DFT calculations and cyclic voltammetry studies.